Investigating the effect of E30 fuel on long term vehicle performance, adaptability and economic feasibility. (15th December 2021) - Alsiyabi, Adil; Stroh, Seth; Saha, Rajib
Highlights: Non-flex fuel vehicles can adapt to 30% ethanol-blended (E30) gasoline. Engine performance is not compromised by E30 consumption. Fuel efficiency of E30 is comparable to that of E15. Significant reduction in CO2 emissions can be achieved through nationwide adoption of E30. Abstract: Due to the drawbacks associated with the use of petroleum derived fuels, the use of more sustainable fuel sources has garnered increasing attention in several sectors including road transportation. However, the transition away from gasoline is often hindered by the inability of currently operating vehicles to efficiently run under alternative fuels. Therefore, the logical short-term alternative is to transition to clean fuel sources including higher-ethanol fuel blends that are compatible with current fuel systems and spark-ignition engines. In this work, the long-term adaptability and economic feasibility of non-flex vehicles to consume a 30% ethanol (E30) fuel blend was investigated. Sixteen diagnostic and operating parameters were tracked in real-time in 50 vehicles over a one-year period. The vast amount of data generated was used to train sparse regression and machine learning models to explore differences in performance and operational robustness of commercial vehicles consuming E30 blends compared to the ones consuming 15% blends. Results indicate that although modest changes can be observed in the behavior of a subset of parameters, overall performance and adaptability are not compromised by consumption of E30. It was determined that an average price difference of 2.5% is sufficient to offset the mileage loss caused by the increased ethanol concentration. Finally, we discuss the large-scale environmental impact of an incremental nation-wide shift towards E30 consumption.